PERANCANGAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) ATAP SEKOLAH CITA BUANA SEBAGAI PENGEMBANGAN NEARLY ZERO ENERGY BUILDING (NZEB) - Ariella, Syafika Safa; Dhofir, Moch.; Wibawa, Unggul (Jurnal Mahasiswa TEUB, 2023)
The development of EBT in Indonesia is still far from the target of the National Energy Policy (KEN), namely the EBT mix of 23% in 2025 and 31% in 2050. One form of EBT development is utilizing solar energy in building technology that has high energy efficiency so that the number of electrical energy consumption is close to zero or called nearly Zero Energy Building (nZEB). Therefore, it is necessary to design the most optimal rooftop solar power plant (PLTS) so that it has good energy production and economic feasibility. To get good energy production, a simulation is carried out using HelioScope software by inputting data on the mechanical and electrical segments so that the amount of energy that can be produced by the rooftop solar power plant is obtained in detail. The results of the simulation of the rooftop solar power plant system that is installed on-grid in HelioScope are composed of 96 monocrystalline solar panels of Trina Solar TSM-DE20-605W (605W) and 3 3-phase inverters of Growatt MID 17KTL-X. The rooftop solar power plant produces an annual production of 84,08 MWh with a performance ratio of 82,1%. Thus, the average percentage of energy supply from rooftop solar power plants is 39,82% or can be said to be good in supplying the electrical energy needs of buildings so that the nZEB can be developed. From the simulation results, the economic feasibility is known, with the Break Even Point (BEP) reached in 12,4 years of the 25 years project period, and the Net Present Value (NPV) and Return on Investment (RoI) are positive, indicating that the rooftop solar power plant is profitable and feasible to develop. Keywords: Rooftop Solar Power Plant, HelioScope, nearly Zero Energy Building, Feasibility Study